Phenylephrine Boluses Vs Noradrenaline Boluses for Hypotension after Spinal Anesthesia in LSCS - Adnan Iqbal, Hafiz Muhammad Javed, Khaleel Ahmad, Muhammad Adeel Ashfaq, Mahnoor Rafique Butt, Marrium Khalid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypotension is a frequent complication highly associated with spinal anesthesia during lower segment cesarean section that imposed adverse effects related to maternal as well as fetal. Purpose: The purpose: of this study is to lighten the comparison of vasopressor (Phenylephrine boluses vs. noradrenaline boluses) use to treat hypotension after spinal anesthesia in LSC patients Study design: randomized double-blind study design. Method: This randomized double-blind study was performed at the department of anesthesia, critical care, and pain medicine at Aziz Bhatti Shaheed Teaching Hospital, Gujrat Pakistan, and was conducted from Jun 2020 to Jun 2021. The patients aged between 20 to 40 years who went through lower segment cesarean section were part of this study. A total of 60 patients were divided into two groups namely groups A and B. Group A contain 30 patients in the same way group occupied with 30 patients and by using a random allocation procedure or protocol, the randomized number was assigned to all patients via the computer-generated system. Group A received phenylephrine and Group B received noradrenaline. Results: Statically analysis was performed using SPSS software. In the case of group A, the mean arterial pressure was measured at 115.03 ± 8.69, heart rate, beats/min was measured at 65.72 ± 9.46, and bradycardia was found in 14 (46.6%) patients out of 30 of group A with a mean value of beats 43.65 ± 3.23, hypotension was found in 4.31 ± 2.11 cases and to treat its repeated episodes with phenylephrine boluses was used 4.21 ± 1.21. In the case of group B, the mean arterial pressure was measured at 121± 9.86, heart rate, beats/min was measured at 80.42± 8.01, and bradycardia was found in 8 (26.6%) patients out of 30 of group B with a mean value of beats 45.23± 2.13, hypotension was found in 2.21± 1.03 cases and to treat its repeated episodes with noradrenaline boluses was used 3.98± 1.32 and all the variables was found with significant results. Conclusion: We conclude that noradrenaline shows ameliorated response to handle the hypotension situation after spinal anesthesia as compared to phenylephrine. Keywords: Spinal anesthesia, phenylephrine bolus, noradrenaline bolus, lower segment cesarean section (LSCS)